The Effect of Oil Prices and Gold Prices on the Indonesia Composite Index with Inflation as an Intervening Variable in Indonesia During the Period 2019-2024 - Almunadia Almunadia; Hakim Muttaqim; M. Saleh (SAINTIS Publishing, 2025)
This study aims to analyze the effect of oil prices and gold prices on the Indonesia Composite Index (ICI) with inflation as an intervening variable in Indonesia during the period of 2019-2024. The data used are secondary data, and the analysis method is Partial Least Squares (PLS). The results demonstrate that oil prices have a significant influence on inflation and the ICI, while gold prices have a significant influence on inflation but not on the ICI. Additionally, inflation does not act as a moderating variable in the relationship between oil prices and gold prices on the ICI. The R-square value of the ICI variable reached 0.809, indicating a strong relationship between the exogenous variables and the ICI, while inflation had an R-square value of 0.193, classified as weak. Based on these findings, fluctuations in oil prices have a more significant impact on the ICI than gold prices, while inflation is not strong enough to moderate this relationship. This study provides insights for policymakers to mitigate the impact of oil price fluctuations on the stock market, as well as for investors to understand the macroeconomic factors influencing the ICI.